A combined biomaterial and cellular approach for annulus fibrosus rupture repair. (February 2015) - Pirvu, Tatiana; Blanquer, Sebastien B.G.; Benneker, Lorin M.; Grijpma, Dirk W.; Richards, Robert G.; Alini, Mauro; Eglin, David; Grad, Sibylle; Li, Zhen
Abstract: Recurrent intervertebral disc (IVD) herniation and degenerative disc disease have been identified as the most important factors contributing to persistent pain and disability after surgical discectomy. An annulus fibrosus (AF) closure device that provides immediate closure of the AF rupture, restores disc height, reduces further disc degeneration and enhances self-repair capacities is an unmet clinical need. In this study, a poly(trimethylene carbonate) (PTMC) scaffold seeded with human bone marrow derived mesenchymal stromal cells (MSCs) and covered with a poly(ester-urethane) (PU) membrane was assessed for AF rupture repair in a bovine organ culture annulotomy model under dynamic load for 14 days. PTMC scaffolds combined with the sutured PU membrane restored disc height of annulotomized discs and prevented herniation of nucleus pulposus (NP) tissue. Implanted MSCs showed an up-regulated gene expression of type V collagen, a potential AF marker, indicating in situ differentiation capability. Furthermore, MSCs delivered within PTMC scaffolds induced an up-regulation of anabolic gene expression and down-regulation of catabolic gene expression in adjacent native disc tissue. In conclusion, the combined biomaterial and cellular approach has the potential to hinder herniation of NP tissue, stabilize disc height, and positively modulate cell phenotype of native disc tissue.